Managing Against the Development of Herbicide Resistant Weeds: Sugarcane - Curtis R. Rainbolt; Brent A. Sellers; Jason A. Ferrell; Gregory E. MacDonald (EDIS, 2006)
Producing a profitable sugarcane crop in Florida depends, in part, on effectively controlling weeds that can reduce yields. Because they provide an efficient and cost effective means of weed control, herbicides are a critical component of sugarcane weed management programs. However, in many cropping systems excessive use of a single herbicide, or group of herbicides with the same site of action, has resulted in the development of herbicide resistant weeds. This document is SS-AGR-244, one of a series of the Agronomy Department, UF/IFAS Extension. Original publication date February 2006.